Pengaruh Likuiditas Dan Struktur Modal Dengan Mediasi Profitabilitas Terhadap Nilai Perusahaan Subsektor Makanan Dan Minuman Yang Terdaftar Di BEI Periode 2018 - 2021 - Purnawan, Lesna (Universitas Tangerang Raya, 2023)
This study aims to investigate the relationship between capital structure, liquidity, and firm value by considering profitability as an intermediary factor. The sample in this study consisted of 13 companies listed on the Indonesia Stock Exchange (IDX) and published financial reports in the food and beverage sector during the 2018-2021 period. This study used a purposive sampling method for sample selection and path analysis using the Smart PLS application as a data analysis method. The findings of this study show several significant results: (1) There is no significant effect between capital structure and profitability, (2) Liquidity has a significant effect on profitability, (3) Capital structure has no significant effect on firm value, (4) Liquidity has an effect on profitability, (5) Profitability has a significant effect on firm value, (6) Profitability does not directly mediate the effect of capital structure and liquidity on firm value.